DAMPAK RESTRIKSI PERDAGANGAN TERHADAP PENAWARAN DAN PERMINTAAN BERAS DI PASAR DUNIA DAN KINERJA PERBERASAN INDONESIA - Julitasari, Evi Nurifah (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The aims of research is to analyze the effect of trade restriction of rice exporter and importer in the open market to influence he world rice supply and demand. Indonesian is the net importer of rice so depend on quantity of market world rice. We use time series data from 1984 to 2007âs and useÂ  simultaneous formulation with econometrical approach.Â  The result show thatâs export restriction will increase the export volume and the world supply but Â the world price will turn exception for United of America Serikat. If there is no-export restriction there is no effect for Indonesianâs rice. ImportÂ  restriction will be increase an import price in all importer country. The effect of no-intervention import restriction will be decrease the domestic production, productivityÂ  and demand fertilizers.Â Â Â Â Â Â Â Â  Suggestion for policy is the intervention in the import restriction is still neccesarry to increase Indonesianâs rice performance. Key words: trade restriction, policy analysis, rice